NEIGHBORING COMMUNITIES: FORIENG EXPIRIENCE AND UKRAINE - Ткаченко, В.С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
This paper examines the experience of the creation of neighborhood communities abroad and in Ukraine. World experience shows that awareness of the citizens of the capacity and capability of the bodies of self-organization of population in cooperation with the local authorities contribute to an effective joint decision of problems of local development. In Ukraine the sphere of neighbouring communities can become ACAH. Key features of the participants of HOAs and members of civil society General - responsibility, activity, ability to self-organization and self-regulation of conduct.